Sexuality, Migration, and Tourism in the 20th Century U.S.-Mexico Borderlands - Medrano, Marlene (History compass, 2013)
The United States-Mexico border is a site in which ethnic and sexual boundaries are constructed and contested. Spatial mobility has profound effects on perceptions and expressions of sexuality. Recent scholarship on the U.S.-Mexico borderlands has illuminated the ways in which migration and tourism influence sexual identities, sexual behavior, and state efforts to monitor sexuality. Further research is essential to understanding these intercultural and cross-class interactions. Furthermore, this is a topic of study that would result in productive interdisciplinary collaboration.